Pengaruh Fasilitas Modal, Inovasi Produk, dan Literasi Digital pada Pengembangan Usaha Mikro, Kecil, dan Menengah di Wilayah Kota Depok - Dwi Laras Novianti; Ari Saptono; Agus Wibowo (eCo-Buss, 2024)
Micro, Small and Medium Enterprises (MSMEs) have a very strategic role in national economic development. The role of MSMEs is very large for economic growth in Indonesia, with a percentage of the number reaching 99% of all business units. Based on data from the Ministry of Cooperatives and MSMEs. Based on data. City opendata.jabarprov.go.id every year there is an increase in the number of MSME business actors, so that competition is increasing and there is a need for excellence. However, there are obstacles experienced, including those related to capital, utilization of social media and online applications in marketing, products that are still monotonous, lack of human resources both in quantity and quality, and constraints in choosing strategic locations. From the problems faced by MSME actors, it causes business actors to have difficulty in developing their businesses. This research was conducted using a survey method using primary data and sampling using the Probability Sampling Method technique. The sample used was 336 respondents, namely MSME business owners in Depok City. The research used path analysis with SPSS application through classical assumption test (normality test, multicollinearity test, and heteroscedasticity test), hypothesis test (coefficient of determination test, F test, and T test), and sobel test. Based on the research results, the variables of capital facilities and digital literacy affect product innovation. The variables of capital facilities, product innovation, and digital literacy affect business development. The variables of capital facilities and digital literacy have an indirect effect on business development through product innovation.